The great cool ranch Dorito in the sky - Galarza, Josh (Henry Holt and Company, 2024)
Fueling all his anxieties into his comic book series, Brett must face the painful truths of his real life and his escalating eating disorder when someone posts his journal--and his deepest insecurities--online.